Dehydration of IPA-H2O mixture: Review of fundamentals and proposal of novel energy-efficient separation schemes. (5th June 2023) - Spatolisano, Elvira; Pellegrini, Laura A.
Highlights: The IPA-water separation has been studied. State-of-the-art for IPA dehydration has been reviewed. Solvent selection criteria have been assessed. Two energy-efficient process configurations have been proposed and analyzed. Abstract: According to the ongoing regulations, the need to identify green and economical production roots for fuels is of paramount importance. Unfortunately, biofuels production is often accompanied with the formation of water, that needs to be removed energy-efficiently. To achieve this separation, extractive and conventional heterogeneous azeotropic distillation have been extensively studied, but these solutions are usually high energy-demanding when non-negligible water content is involved. In view of introducing significant energy savings for the alcohol dehydration, this work focuses on the analysis of two innovative separation schemes: one based on heterogeneous azeotropic distillation with binary azeotrope and the other based on liquid–liquid extraction combined with distillation. For the sake of example, the proposed alternatives have been applied to the isopropanol-water mixture. The performances of the new configurations are assessed in terms of energy consumption and compared with conventional heterogeneous azeotropic distillation, proving the energy saving of the two proposed layouts.